Tin-copper alloy and tin-copper alloy laser cladding process

By introducing specific elements and process processing into tin-copper alloys, the problems of low energy utilization and high pore generation in traditional laser cladding processes are solved, and higher energy utilization and lower porosity are achieved, and molding accuracy and wear resistance are improved.

CN119685818AActive Publication Date: 2025-03-25NINGBO HAITIAN LASER MACHINERY MANUFACTURING CO LTD
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202510185477.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-20
Publication Date
2025-03-25
Estimated Expiration
2045-02-20

AI Technical Summary

Technical Problem

When preparing highly dense copper alloy parts, traditional laser cladding processes have problems such as low energy utilization, frequent pore generation and melt instability, which affect the molding accuracy and quality.

Method used

A tin copper alloy is used, which contains Sn 11%-13%, P 0.05%-2.0%, Ni 0.5%-5.0%, Cr 0.5%-3.5%, and rare earth elements. By introducing rare earth elements and chromium elements, the melt viscosity is adjusted, the melt stability is maintained, and La and Ce are added in the form of phosphorus copper spheres to protect the elements and reduce the generation of pores.

Benefits of technology

The energy utilization rate of the laser cladding process is improved, the generation of pores is reduced, and the wear resistance and molding accuracy of tin and copper alloys are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119685818A_ABST
    Figure CN119685818A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of tin bronze laser cladding forming processes, in particular to a tin-copper alloy and a tin-copper alloy laser cladding process. The tin-copper alloy comprises, by mass, 11%-13% of Sn, 0.05%-2.0% of P, 0.5%-5.0% of Ni, 0.5%-3.5% of Cr, 0.2%-2.0% of rare earth elements and the balance copper and unremovable impurities, the rare earth elements are a mixture of La and Ce, La, Ce and P are added in the form of phosphorus copper balls, and the particle size of finished product powder of the tin-copper alloy ranges from 50 micrometers to 120 micrometers. According to the tin-copper alloy and the tin-copper alloy laser cladding process, the energy utilization rate is extremely high, and meanwhile the porosity is lower.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of tin-bronze laser cladding forming technology, and more specifically, it relates to a tin-copper alloy and a tin-copper alloy laser cladding technology. Background Art

[0002] The SLM method, or selective laser melting, is a metal additive manufacturing technology that uses a high-energy laser beam to melt and stack metal powder layer by layer to eventually construct a complete metal part. However, the use of the SLM method to prepare highly dense copper alloy parts is still very challenging. First, due to the high optical reflectivity of copper to infrared, the energy required for the dense part increases exponentially, which means that a higher-power laser is required. At the same time, higher copper back reflections can also damage the optical components of the equipment. Second, the high intrinsic thermal conductivity of copper causes the absorbed heat to dissipate quickly, and in order to melt the material, more energy needs to be input.

[0003] Moreover, high laser reflectivity and high thermal conductivity are prone to non-fusion pores between passes and layers during the laser forming process. Excessive energy input reduces the melt viscosity, making violent boiling and spheroidization prone to occur, resulting in an unstable molten pool and metallurgical defects, which affect the forming accuracy and quality and reduce its service performance.

[0004] In summary, the traditional laser cladding process still has the defects of low capacity utilization and easy generation of pores. Summary of the invention

[0005] In order to improve the energy utilization rate of the laser cladding process and reduce the generation of pores, the present application provides a tin-copper alloy and a tin-copper alloy laser cladding process.

[0006] In a first aspect, the present application provides a tin-copper alloy, which adopts the following technical solution: A tin-copper alloy comprises the following raw materials in percentage by mass: Sn 11%-13%, P 0.05%-2.0%, Ni 0.5%-5.0%, Cr 0.5%-3.5%, rare earth elements 0.2-2.0%, and the balance is copper and impurities that cannot be removed. The rare earth elements are a mixture of one or two of La and Ce. La, Ce and P are added in the form of phosphor copper balls. The finished powder particle size of the tin-copper alloy is between 50-120 μm.

[0007] Preferably, the rare earth element is a mixture of La and Ce.

[0008] Preferably, the tin-copper alloy comprises the following raw materials in percentage by mass: Sn 11%-13%, P 0.05%-2.0%, Ni 0.5%-5.0%, Cr 0.5%-3.5%, La 0.1%-1.0% and Ce0.1-1.0%, the balance is copper and unremovable impurities, La, Ce and P are added in the form of phosphor copper balls, and the finished powder particle size of the tin-copper alloy is between 50-120μm.

[0009] In order to effectively improve the energy utilization rate of the laser cladding process, the applicant first considered using a short-wavelength green laser as the light source to increase the energy absorption rate of copper. However, the price of green lasers is relatively high, resulting in a relatively low cost performance and poor precision control, so there is still room for improvement.

[0010] To this end, the applicant thought of using powder raw materials with relatively smaller particle sizes, which can improve the energy absorption rate and the molding accuracy at the same time. However, the preparation of fine powder will lead to an increase in porosity, which in turn will lead to deterioration of the mechanical properties, corrosion resistance and conductivity of the tin-copper alloy.

[0011] In order to improve the defect of increased porosity of tin-copper alloy caused by using small-particle powder raw materials, the applicant first thought of using PVD evaporation to modify the raw material powder, thereby reducing the porosity during the tin-copper alloy laser forming process. However, the PVD evaporation process is complicated and is not conducive to large-scale application.

[0012] To this end, the applicant thought of introducing rare earth elements that reduce melt viscosity and chromium elements that increase melt viscosity into the tin-copper alloy powder, and using a competitive mechanism to adjust the viscosity of the tin-bronze melt during laser forming, maintain melt stability, and then promote the floating discharge of the original pores to achieve the purpose of reducing pores. At the same time, taking advantage of the low solubility of rare earth elements and chromium elements in copper and the large difference in melting points, precipitation strengthening phases are precipitated in situ to inhibit grain growth and thus improve wear resistance.

[0013] When the rare earth element is a mixture of La and Ce, since La and Ce have a strong affinity for hydrogen and oxygen, they can capture the oxygen of an oxide in the tin-copper metal liquid, thereby forming a large number of La2O3, Ce2O3, La(OH)3, and Ce(OH)3 particles, thereby refining the macroscopic structure of the tin-copper alloy.

[0014] At the same time, with the addition of La and Ce, due to their alloying effect, the supercooling of the tin-copper alloy increases, and the microstructure of the alloy depends on the supercooling of the growth process and growth conditions, that is, under this condition, the secondary dendrite spacing of the tin-copper alloy becomes smaller. In addition, during the growth of the tin-copper alloy phase, La and Ce will also gather around the tin-copper alloy phase, reducing the solid-liquid surface tension, increasing the supercooling of the solid-liquid interface front component, and further promoting the refinement of the dendrite.

[0015] Compared with the use of La or Ce alone, the mixed use of La and Ce can promote the formation of more La2O3, Ce2O3, La(OH)3, and Ce(OH)3 particles, thereby making the macrostructure and microstructure of the tin-copper alloy more refined, ultimately resulting in a lower porosity.

[0016] Moreover, when La and Ce adopt the above-mentioned mass percentages, more La2O3, Ce2O3, La(OH)3, and Ce(OH)3 particles will be formed in the tin-copper alloy, thereby making the macrostructure and microstructure of the tin-copper alloy more refined, ultimately resulting in a lower porosity.

[0017] Preferably, the preparation method of the tin-copper alloy finished powder is as follows: first, copper, tin, nickel and chromium are added to a vacuum melting crucible, and the metal is melted by induction heating. When the temperature of the molten metal reaches 1000-1300°C, phosphor copper and rare earth elements are added to the molten metal by secondary feeding, and then the molten metal is kept warm for 5-30 minutes. Finally, the molten metal is poured into a tundish crucible and the molten metal is prepared into spherical metal powder by gas atomization, and finally cooled and gas-graded to obtain the tin-copper alloy finished powder.

[0018] When the smelting temperature is between 1000-1300℃, the yield of the finished tin-copper alloy powder is relatively higher. However, since phosphorus and rare earth elements are easily burned, long-term smelting will make the ratio of elements difficult to control. Therefore, the secondary feeding method can promote the melting of phosphorus and rare earth elements in a short time, thereby ensuring the balance of elements and ultimately obtaining a better pore inhibition effect.

[0019] Preferably, the preparation method of the phosphor copper ball is as follows: first, the phosphor copper alloy is added into a vacuum melting crucible, and the metal is melted by induction heating. When the temperature of the molten metal reaches 1000-1300°C, La and Ce are added to melt and mix evenly to obtain a phosphor copper melt, and then the phosphor copper melt is cooled and crystallized into a phosphor copper rod by a continuous casting machine, and then the phosphor copper rod is processed into a phosphor copper ball by a ball upsetting machine, a polishing machine, a cleaning machine and a packaging machine in sequence.

[0020] In the present application, La, Ce and P are added in the form of phosphor copper balls, which enable the phosphor copper balls to continuously protect La, Ce and P, further reduce the possibility of burning of La, Ce and P, and indirectly enable the tin-copper alloy to obtain a lower porosity.

[0021] Preferably, in the preparation of spherical metal powder by the aerosol method, high-purity argon is used as the atomizing gas, the pressure difference between the smelting chamber and the aerosol chamber is less than 0.3 MPa, and the pressure of the high-pressure atomizing gas is 4-5 MPa.

[0022] In a second aspect, the present application provides a tin-copper alloy laser cladding process, which adopts the following technical solution: A tin-copper alloy laser cladding process, which uses laser cladding to attach the finished powder of the tin-copper alloy to a component; The laser cladding adopts a narrow spot, the laser spot diameter is 5mm, the laser power is 1500-3000 kilowatts, and the cladding speed is 400-800mm / min; After forming, the components are cut, ground and polished.

[0023] A tin-copper alloy laser cladding process, which uses laser cladding to attach the finished powder of the tin-copper alloy to a component; The laser cladding adopts a wide spot, the laser spot size is 20mm×4mm, the laser power is 8000-15000 kilowatts, and the cladding speed is 200-600mm / min; After forming, the components are cut, ground and polished.

[0024] In laser cladding, if the laser power is too low, the molten pool is not obvious, resulting in the generation of pores, but there is not enough time to discharge the pores. If the laser power is too high, too many pores are generated and cannot be discharged. If the cladding speed is too slow, the efficiency is reduced and the dilution rate is too high; if the cladding speed is too fast, the efficiency of pore discharge is affected, resulting in pores.

[0025] To this end, the applicant conducted a large number of tests and found that for equipment with a 5mm diameter spot, the laser power is 1500-3000 kilowatts and the cladding speed is 400-800mm / min, which is more suitable; for equipment with a 20mm×4mm rectangular spot, the laser power is 8000-15000 kilowatts and the cladding speed is 200-600mm / min, which is more suitable.

[0026] In summary, this application has the following beneficial effects: 1. This application introduces rare earth elements that reduce melt viscosity and chromium elements that increase melt viscosity into tin-copper alloy powder, and uses a competitive mechanism to adjust the viscosity of the tin-bronze melt during laser forming, maintain melt stability, and then promote the floating discharge of native pores to achieve the purpose of reducing pores. At the same time, taking advantage of the low solubility of rare earth elements and chromium elements in copper and the large difference in melting points, precipitation strengthening phases are precipitated in situ to inhibit grain growth, thereby improving wear resistance; At the same time, when the smelting temperature is between 1000-1300℃, the yield of the finished powder of tin-copper alloy is relatively higher. However, since phosphorus and rare earth elements are easily burned, long-term smelting will make the ratio of elements difficult to control. Therefore, the secondary feeding method can promote the melting of phosphorus and rare earth elements in a short time, thereby ensuring the balance of elements and finally obtaining a better pore inhibition effect. Furthermore, La, Ce and P are added in the form of phosphor copper balls, which enable the phosphor copper balls to continuously protect La, Ce and P, further reducing the possibility of burning of La, Ce and P, and indirectly enabling the tin-copper alloy to obtain a lower porosity.

[0027] 2. When the rare earth element is a mixture of La and Ce, La and Ce have a strong affinity for hydrogen and oxygen, so they can take away the oxygen of an oxide in the tin-copper metal liquid, thereby forming a large number of La2O3, Ce2O3, La (OH) 3, Ce (OH) 3 particles, thereby refining the macroscopic structure of the tin-copper alloy; At the same time, with the addition of La and Ce, the supercooling of the tin-copper alloy increases due to its alloying effect, and the microstructure of the alloy depends on the supercooling of its growth process and growth conditions, that is, under this condition, the secondary dendrite spacing of the tin-copper alloy becomes smaller; In addition, during the growth of the tin-copper alloy phase, La and Ce will also gather around the tin-copper alloy phase, reducing the solid-liquid surface tension, increasing the supercooling of the components at the solid-liquid interface front, and further promoting the refinement of the dendrites.

[0028] 3. In laser cladding, if the laser power is too small, the molten pool is not obvious, resulting in the generation of pores, but there is not enough time to discharge the pores. If the laser power is too large, too many pores will be generated and cannot be discharged. The cladding speed is too slow, the efficiency is reduced and the dilution rate is too high; the cladding speed is too fast, which affects the efficiency of pore discharge and causes pores. To this end, the applicant conducted a large number of tests and found that for equipment with a 5mm diameter spot, the laser power is 1500-3000 kilowatts and the cladding speed is 400-800mm / min, which is more suitable; for equipment with a 20mm×4mm rectangular spot, the laser power is 8000-15000 kilowatts and the cladding speed is 200-600mm / min, which is more suitable.

[0029] 4. The tin-copper alloy of the present application has good adaptability to laser cladding. At the same time, the parameter window of the laser cladding process is wide, which can effectively improve the impact of equipment noise or environmental changes on the uniformity of coating quality. Moreover, the elements of the tin-copper alloy are environmentally friendly and harmless. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 is a diagram of the pore situation of Example 1; Figure 2 It is the pore situation diagram of comparative example 1; Figure 3 is a diagram of the pore situation of Example 2; Figure 4 This is a diagram of the pore situation of Comparative Example 2. DETAILED DESCRIPTION

[0031] The following combination Figure 1-Figure 4 , Examples 1-9 and Comparative Examples 1-2 further illustrate the present application in detail.

[0032] raw material:

[0033] Cu copper, P-Cu phosphorus copper, Sn tin, Ni nickel, Cr chromium, La lanthanum and Ce cerium are all commonly available on the market.

[0034] Example 1

[0035] A tin-copper alloy comprises the following raw materials in percentage by mass: Sn 12.0%, P 1.0%, Ni 2.0%, Cr 1.0%, La 0.3%, Ce 0.3%, and the balance is copper and unremovable impurities; The preparation method of the tin-copper alloy finished powder is as follows: first, 78.9 kg of copper, 12 kg of tin, 2 kg of nickel and 1 kg of chromium are added into a vacuum melting crucible, the vacuum is evacuated to 10 Pa, medium frequency induction melting is adopted, the melting power is 150 kilowatts, after melting for 90 minutes, the metal is completely melted, and the temperature of the molten metal is measured by an infrared dual colorimetric thermometer; When the temperature of the melt reaches 1150°C, phosphor copper balls are added to the molten metal by secondary feeding, and then the temperature is kept for 15 minutes. After the molten metal is clarified, the molten metal is poured into the tundish crucible. The temperature of the tundish is 1000°C. At the same time, high-pressure gas is turned on for atomization, and the molten metal is atomized into spherical metal droplets and rapidly cooled and solidified. After complete cooling, the powder is subjected to airflow classification, and the part with a particle size of 50-120μm is selected, which is the finished tin-copper alloy powder; In the preparation of spherical metal powder by the aerosol method, high-purity argon is used as the atomizing gas, the pressure difference between the melting chamber and the aerosol chamber is less than 0.3 MPa, and the pressure of the high-pressure atomizing gas is 5 MPa.

[0036] The phosphor copper ball is composed of phosphor copper, lanthanum and cerium, with the content of 5.5kg phosphor copper, 0.3kg lanthanum and 0.3kg cerium. The preparation method of phosphor bronze ball is as follows: First, add the phosphor copper alloy into a vacuum melting crucible and melt the metal by induction heating. When the temperature of the molten metal reaches 1150°C, add lanthanum and cerium and melt and mix them evenly to obtain phosphor copper melt. Then, the phosphor copper melt is cooled and crystallized into phosphor copper rods through a continuous casting machine. The phosphor copper rods are then processed into phosphor copper balls through a ball upsetting machine, a polishing machine, a cleaning machine and a packaging machine in sequence.

[0037] A tin-copper alloy laser cladding process, which uses laser cladding to attach the finished powder of the tin-copper alloy to a component; Laser cladding uses a narrow spot, with a laser spot diameter of 5 mm, a laser power of 2100 kW, and a cladding speed of 600 mm / min; After forming, the components are cut, ground and polished.

[0038] Example 2

[0039] A tin-copper alloy comprises the following raw materials in percentage by mass: Sn 12.0%, P 1.0%, Ni 2.0%, Cr 1.5%, La 0.5%, Ce 0.5%, and the balance is copper and impurities that cannot be removed; The preparation method of the tin-copper alloy finished powder is as follows: first, 78 kg of copper, 12 kg of tin, 2 kg of nickel, and 1.5 kg of chromium are added into a vacuum melting crucible, and the vacuum is evacuated to 10 Pa, and medium frequency induction melting is adopted, and the melting power is 150 kilowatts. After melting for 90 minutes, all the metals are melted, and the temperature of the molten metal is measured by an infrared dual colorimetric thermometer; When the temperature of the melt reaches 1150°C, phosphor copper balls are added to the molten metal by secondary feeding, and then the temperature is kept for 15 minutes. After the molten metal is clarified, the molten metal is poured into the tundish crucible. The temperature of the tundish is 1000°C. At the same time, high-pressure gas is turned on for atomization, and the molten metal is atomized into spherical metal droplets and rapidly cooled and solidified. After complete cooling, the powder is subjected to airflow classification, and the part with a particle size of 50-120μm is selected, which is the finished tin-copper alloy powder; The phosphor copper ball is composed of phosphor copper, lanthanum and cerium, with the content of 5.5kg phosphor copper, 0.5kg lanthanum and 0.5kg cerium. The preparation method of phosphor bronze ball is as follows: First, add the phosphor copper alloy into a vacuum melting crucible and melt the metal by induction heating. When the temperature of the molten metal reaches 1150°C, add lanthanum and cerium and melt and mix them evenly to obtain phosphor copper melt. Then, the phosphor copper melt is cooled and crystallized into phosphor copper rods through a continuous casting machine. The phosphor copper rods are then processed into phosphor copper balls through a ball upsetting machine, a polishing machine, a cleaning machine and a packaging machine in sequence.

[0040] A tin-copper alloy laser cladding process, which uses laser cladding to attach the finished powder of the tin-copper alloy to a component; Laser cladding uses a wide spot, the laser spot size is 20mm×4mm, the laser power is 8500 kilowatts, and the cladding speed is 400mm / min; After forming, the components are cut, ground and polished.

[0041] Example 3

[0042] The difference from Example 1 is that the phosphor bronze balls are added directly without secondary addition treatment.

[0043] Example 4

[0044] The difference from Example 1 is that phosphor copper, lanthanum and cerium are added directly without phosphor copper ball treatment.

[0045] Example 5

[0046] The difference from Example 4 is that no lanthanum is added and the missing part is supplemented by copper.

[0047] Example 6

[0048] The difference from Example 4 is that no cerium is added and the missing part is supplemented by copper.

[0049] Example 7-Example 8

[0050] The difference from Example 4 is that the mass percentages of lanthanum and cerium are different, as shown in Table 1.

[0051] Table 1 Mass percentage of each component of rare earth element in Example 4 and Example 7-Example 8

[0052] Example 9

[0053] The difference from Example 4 is that the rare earth elements lanthanum and cerium are no longer added.

[0054] Comparative Example 1

[0055] The difference from Example 1 is that Cr, La and Ce are no longer added to the tin-copper alloy, and the missing parts are supplemented by copper.

[0056] Comparative Example 2

[0057] The difference from Example 2 is that Cr, La and Ce are no longer added to the tin-copper alloy, and the missing parts are supplemented by copper.

[0058] Performance testing

[0059] Tin-Copper Alloy Porosity Test Three samples were taken from Examples 1 to 9 and Comparative Examples 1 to 2, respectively, and the porosity of the samples was tested and the average value was taken according to ASTM B276-05 (2015) "Standard Test Method for Apparent Porosity of Cemented Carbide".

[0060] The test data are shown in Table 2.

[0061] Table 2 Test data table of Example 1-Example 9 and Comparative Example 1-Comparative Example 2

[0062] In order to effectively improve the energy utilization rate of the laser cladding process, the applicant first considered using a short-wavelength green laser as the light source to increase the energy absorption rate of copper. However, the price of green lasers is relatively high, resulting in a relatively low cost performance and poor precision control, so there is still room for improvement.

[0063] To this end, the applicant thought of using powder raw materials with relatively smaller particle sizes, which can improve the energy absorption rate and the molding accuracy at the same time. However, the preparation of fine powder will lead to an increase in porosity, which in turn will lead to deterioration of the mechanical properties, corrosion resistance and conductivity of the tin-copper alloy.

[0064] In order to improve the defect of increased porosity of tin-copper alloy caused by using small-particle powder raw materials, the applicant first thought of using PVD evaporation to modify the raw material powder, thereby reducing the porosity during the tin-copper alloy laser forming process. However, the PVD evaporation process is complicated and is not conducive to large-scale application.

[0065] In the tin-copper alloy powder, rare earth elements that reduce melt viscosity and chromium elements that increase melt viscosity are introduced. The viscosity of the tin-bronze melt during laser forming is adjusted by a competitive mechanism to maintain melt stability, thereby promoting the floating and discharge of native pores to achieve the purpose of reducing pores. At the same time, the characteristics of rare earth elements and chromium elements with low solubility in copper and large melting point difference are used to precipitate precipitation strengthening phase in situ to inhibit grain growth.

[0066] Specifically, refer to Example 1-Example 2, Comparative Example 1-Comparative Example 2 and Table 2 and combine Figure 1-Figure 2 It can be seen that the porosity of Examples 1 and 2 is significantly reduced compared with Comparative Examples 1 and 2, which indicates that the addition of Cr, La and Ce can effectively reduce the generation of bubbles in the tin-copper alloy.

[0067] In addition, in laser cladding, if the laser power is too small, the molten pool is not obvious, resulting in the generation of pores, but there is not enough time to discharge the pores. If the laser power is too large, too many pores are generated and cannot be discharged. If the cladding speed is too slow, the efficiency is reduced and the dilution rate is too high; if the cladding speed is too fast, the efficiency of pore discharge is affected, resulting in pores.

[0068] To this end, the applicant conducted a large number of tests and found that for equipment with a 5mm diameter spot, the laser power is 1500-3000 kilowatts and the cladding speed is 400-800mm / min, which is more suitable; for equipment with a 20mm×4mm rectangular spot, the laser power is 8000-15000 kilowatts and the cladding speed is 200-600mm / min, which is more suitable.

[0069] Referring to Example 1 and Example 3 and combining with Table 2, it can be seen that the porosity of Example 3 is significantly improved compared with that of Example 1, which shows that, compared with directly adding phosphor copper balls, secondary addition of phosphor copper balls can further reduce the generation of pores in the tin-copper alloy.

[0070] The reason is that when the smelting temperature is between 1000-1300℃, the yield of the finished tin-copper alloy powder is relatively higher. However, since phosphorus and rare earth elements are easily burned, long-term smelting will make the ratio of elements difficult to control. Therefore, the secondary feeding method can promote the melting of phosphorus and rare earth elements in a short time, thereby ensuring the balance of elements and ultimately obtaining a better pore inhibition effect.

[0071] Referring to Example 1 and Example 4 and combining with Table 2, it can be seen that the porosity of Example 4 is significantly improved compared with that of Example 1, which shows that adding La, Ce and P in the form of phosphor copper balls can further reduce the generation of pores in the tin-copper alloy.

[0072] The reason is that when La, Ce and P are added in the form of phosphor copper balls, the phosphor copper balls will continue to protect La, Ce and P, effectively reducing the possibility of burning of La, Ce and P, and indirectly causing the tin-copper alloy to obtain a lower porosity.

[0073] Referring to Example 4-Example 6 and combining with Table 2, it can be seen that compared with Example 4, Example 5-Example 6 has a relatively higher porosity, which shows that compared with using lanthanum or cerium alone, when lanthanum and cerium are used together, the prepared tin-copper alloy will have a lower porosity.

[0074] The reason is that when the rare earth elements are a mixture of La and Ce, La and Ce have a strong affinity for hydrogen and oxygen, so they can capture the oxygen of an oxide in the tin-copper metal liquid, thereby forming a large number of La2O3, Ce2O3, La(OH)3, Ce(OH)3 particles, thereby refining the macroscopic structure of the tin-copper alloy.

[0075] At the same time, with the addition of La and Ce, due to their alloying effect, the supercooling of the tin-copper alloy increases, and the microstructure of the alloy depends on the supercooling of the growth process and growth conditions, that is, under this condition, the secondary dendrite spacing of the tin-copper alloy becomes smaller. In addition, during the growth of the tin-copper alloy phase, La and Ce will also gather around the tin-copper alloy phase, reducing the solid-liquid surface tension, increasing the supercooling of the solid-liquid interface front component, and further promoting the refinement of the dendrite.

[0076] Compared with the use of La or Ce alone, the mixed use of La and Ce can promote the formation of more La2O3, Ce2O3, La(OH)3, and Ce(OH)3 particles, thereby making the macrostructure and microstructure of the tin-copper alloy more refined, ultimately resulting in a lower porosity.

[0077] Referring to Example 4 and Example 7-Example 8 and combining with Table 2, it can be seen that the porosity of Example 7-Example 8 is significantly improved compared with Example 4, which shows that when lanthanum and cerium use the mass percentage of Example 4, the prepared tin-copper alloy will have a lower porosity.

[0078] The reason may be that when La and Ce adopt the above-mentioned mass percentages, more La2O3, Ce2O3, La(OH)3, and Ce(OH)3 particles will be formed in the tin-copper alloy, thereby making the macrostructure and microstructure of the tin-copper alloy more refined, ultimately resulting in a lower porosity.

[0079] Referring to Example 4 and Example 9 and combining with Table 2, it can be seen that the porosity of Example 9 is significantly improved compared with that of Example 4, which further illustrates that the addition of lanthanum and cerium can effectively reduce the porosity of the tin-copper alloy.

[0080] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A tin-copper alloy, characterized in that: The following raw materials are included in mass percentage: Sn 11%-13%, P 0.05%-2.0%, Ni 0.5%-5.0%, Cr 0.5%-3.5%, rare earth elements 0.2-2.0%, the balance is copper and unremovable impurities, the rare earth elements are a mixture of La and Ce, La, Ce and P are added in the form of phosphor copper balls, and the finished powder particle size of the tin-copper alloy is between 50-120μm.

2. The tin-copper alloy according to claim 1, characterized in that: The following raw materials are included in mass percentage: Sn 11%-13%, P 0.05%-2.0%, Ni 0.5%-5.0%, Cr 0.5%-3.5%, La 0.1%-1.0% and Ce 0.1-1.0%, the balance is copper and unremovable impurities, La, Ce and P are added in the form of phosphor copper balls, and the finished powder particle size of the tin-copper alloy is between 50-120μm.

3. The tin-copper alloy according to claim 2, characterized in that: The preparation method of the tin-copper alloy finished powder is as follows: First, copper, tin, nickel and chromium are added into a vacuum melting crucible, and the metal is melted by induction heating. When the temperature of the molten metal reaches 1000-1300°C, phosphor copper, lanthanum and cerium are added into the molten metal by secondary feeding, and then the molten metal is kept warm for 5-30 minutes. Finally, the molten metal is poured into a tundish crucible and the molten metal is prepared into spherical metal powder by gas atomization. Finally, it is cooled and airflow graded to obtain a finished tin-copper alloy powder.

4. The tin-copper alloy according to claim 1, characterized in that: The preparation method of the phosphor bronze ball is: First, add the phosphor copper alloy into a vacuum melting crucible and melt the metal by induction heating. When the temperature of the molten metal reaches 1000-1300℃, add La and Ce to melt and mix evenly to obtain phosphor copper melt. Then, the phosphor copper melt is cooled and crystallized into phosphor copper rods through a continuous casting machine. The phosphor copper rods are then processed into phosphor copper balls through a ball upsetting machine, a polishing machine, a cleaning machine and a packaging machine in sequence.

5. The tin-copper alloy according to claim 3, characterized in that: In the preparation of spherical metal powder by the aerosol method, high-purity argon is used as the atomizing gas, the pressure difference between the melting chamber and the aerosol chamber is less than 0.3MPa, and the pressure of the high-pressure atomizing gas is 4-5MPa.

6. A tin-copper alloy laser cladding process, characterized in that: The finished powder of the tin-copper alloy according to any one of claims 1 to 5 is attached to the component by laser cladding; The laser cladding adopts a narrow spot, the laser spot diameter is 5mm, the laser power is 1500-3000 kilowatts, and the cladding speed is 400-800mm / min; After forming, the components are cut, ground and polished.

7. A tin-copper alloy laser cladding process, characterized in that: The finished powder of the tin-copper alloy according to any one of claims 1 to 5 is attached to the component by laser cladding; The laser cladding adopts a wide spot, the laser spot size is 20mm×4mm, the laser power is 8000-15000 kilowatts, and the cladding speed is 200-600mm / min; After forming, the components are cut, ground and polished.

Citation Information

Patent Citations

  • Cu powder applied to laser cladding of P-Cu work piece, and cladding method

    CN111687407A

  • Method and device for oscillating laser-induction composite cladding of wear-resistant and ablation-resistant copper-based coating

    CN113005446A

  • Copper-based alloy powder, preparation method and application of copper-based alloy powder, chromium-rich precipitated phase copper-based alloy cladding layer and preparation method and application of chromium-rich precipitated phase copper-based alloy cladding layer

    CN116790933A

  • Superconducting strip copper plating method

    CN117248256A

  • High-temperature-resistant and wear-resistant copper alloy coating and preparation method thereof

    CN117684164A